Drug resistance detection and mutation patterns of multidrug resistant tuberculosis strains from children in Delhi. Issue 2 (June 2017) - Arora, Jyoti; Singhal, Ritu; Bhalla, Manpreet; Verma, Ajoy; Singh, Niti; Behera, Digamber; Sarin, Rohit; Myneedu, Vithal Prasad
Abstract: A total of 312 sputum samples from pediatric patients presumptive of multidrug resistant tuberculosis were tested for the detection of drug resistance using the GenoTypeMTBDRplus assay. A total of 193 (61.8%) patients were smear positive and 119 (38.1%) were smear negative by Ziehl–Neelsen staining. Line probe assay (LPA) was performed for 208 samples/cultures (193 smear positive samples and 15 cultures from smear negative samples). Valid results were obtained from 198 tests. Of these, 125/198 (63.1%) were sensitive to both rifampicin (RIF) and isoniazid (INH). 73/198 (36.9%) were resistant to at least INH/RIF, out of which 49 (24.7%) were resistant to both INH and RIF (multidrug resistant). Children with tuberculosis are often infected by someone close to them, so strengthening of contact tracing in the program may help in early diagnosis to identify additional cases within the household. There is a need to evaluate newer diagnostic assays which have a high sensitivity in the case of smear negative samples, additional samples other than sputum among young children not able to expectorate, and also to fill the gap between estimated and reported cases under the program.